Influence of nicotine dependence, current smoking status and gender on CYP1A1, CYP1B1 and CYP2A6 expression in oral squamous cell carcinoma - Almeida, Adriana Ávila [UNESP]; Bandeira, Celso Muller [UNESP]; Alves, Mônica Ghislaine Oliveira [UNESP]; Pascoal, Maria Beatriz Nogueira; Chagas, José Francisco Salles; Bernardino Neto, Morun; Barros, Patrícia Pimentel de [UNESP]; Nunes, Fábio Daumas; Carta, Celina Faig Lima [UNESP]; Almeida, Janete Dias [UNESP] (Editora Cubo, 2022)
Objective: Tobacco smoke is composed of cancer-causing chemicals referred to as carcinogens. These carcinogens are metabolized by the enzymes of the cytochrome P450 (CYP) family. Our objective was to evaluate the correlation of tobacco consumption parameters with CYP1A1, CYP1B1 and CYP2A6 expression using qRT-PCR in samples of oral squamous cell carcinoma (OSCC). Material and Methods: The sample was divided into 2 groups: Cancer (36 subjects) and non-Cancer (12 subjects). The smokers’ participants (36) were evaluated regarding their Nicotine dependence (ND) was assessed by the Fagerström test for cigarette dependence (FTCD). Questions regarding tobacco consumption like the number of cigarettes/day (CPD), duration of use, and pack-years were also evaluated. The Mann-Whitney and Spearman correlation tests were used at a significance level of 5%. Results: 48 participants were included, 32 men (66.7%), 36 smokers (75%) and 27 smokers with OSCC (56.3%). Samples of OSCC expressed more CYP1A1, CYP1B1, and CYP2A6. Especially, the CYP1B1 gene was significantly expressed in OSCC samples, regardless gender or tobacco use. No women expressed CYP2A6, as well as, non-smokers did not express the CYP1A1 and CYP2A6 genes. CYP1A1 gene was higher among men (P = 0.021). Conclusion: Lack of exposure to tobacco may justify the absence of CYP1A1 and CYP2A6 expression in non-smokers. The CYP1B1 gene was significantly expressed in the cancer presence despite gender or tobacco use. The assessment of ND and quantification of tobacco consumption are important instruments in monitoring smokers with benign oral lesions and, especially, in the presence of cancer.
Influência da dependência nicotínica, parâmetros de consumo de tabaco e gênero na expressão de CYP1A1, CYP1B1 e CYP2A6 em carcinoma de células escamosas oral
Keywords: Carcinoma; CYP1A1; CYP1B1; CYP2A6; Squamous cell; Tobacco use disorder